Case Report: RNF213 variant and choroidal anastomosis as potential risk factors for early stroke in moyamoya syndrome associated with Down syndrome - Yamamoto, Keisuke; Kaku, Yasuyuki; Koga, Hiroshi (Frontiers in Pediatrics, 2023)
Introduction: Recent studies have suggested associations between RNF213 variants and the formation of periventricular anastomosis among patients with moyamoya disease, leading to early onset of cerebral hemorrhage and rebleeding.We report herein the case of a boy with Down syndrome and moyamoya syndrome. Exome sequencing identified a heterozygous RNF213 R4810K variant. After ischemic stroke occurred at 9 years old, indirect surgical revascularization was performed for the left cerebral hemisphere and improved ischemic symptoms and cerebral hypoperfusion, while the left choroidal anastomosis remained. At 13 years old, he presented with left thalamic hemorrhage attributed to the anterior choroidal artery, with rebleeding observed four days after the initial hemorrhage under strict blood pressure control. The patient was discharged without neurological deficits 20 days after the hemorrhagic stroke.Presence of an RNF213 variant and choroidal anastomosis may represent risk factors for cerebral hemorrhage in patients with Down syndrome and moyamoya syndrome, as well as in patients with moyamoya disease.